The Institutional Advertising of the Andalusian Government - Fernández Poyatos, Mª Dolores; Feliu García, Emilio (Pensar la Publicidad. Revista Internacional de Investigaciones Publicitarias, 2012)
Since the advertising insertions done by the Andalusian Committee during the period of 1999-2009, it is analyzed the evolution of the Andalusian governmental advertising in several fields (Social, Political, Corporate and Commercial). This evolution is also studied in sectors of the institutional advertising, focusing the attention in three main issues: when, where and about what does the Committee make advertising of. The objective of this research, which results are presented in this work, is to clarify the behavior of the Andalusian Committee as advertiser.